The Power Of Social Media: How Trust Impacts Online Buying Decisions In The Digital Era - Utama, Satria Putra; Sari, Risca Kurnia; Arsiyanto, M. Tody (Jurnal Ekonomi, 2024)
This research aims to investigate the impact of social media marketing affects Purchase Intention, taking into account e-trust as a mediating factor. The data was collected from 200 participants using purposive sampling and a quantitative approach during the research. The data was analyzed using Structural Equation Modeling (SEM), which was collected through questionnaires. The SEM analysis results indicate that social media marketing (X) influences e-trust (Z) and purchase intention (Y). The impact of e-trust (Z) on purchase intention (Y) is evident, and the analysis using structural equation modeling (SEM) shows that the results suggest that the indirect influence through e-trust (Z) is more significant than the direct influence on the purchase intention variable (Y). Consequently, the e-trust (Z) variable could potentially serve as a mediator for the impact of Social Media Marketing (X) on purchase intention (Y)